2005
DOI: 10.1097/01.bsd.0000143312.08303.5d
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Heating of Painful Annular Disruptions

Abstract: Radiofrequency heating of annular tears can lead to an improvement in the pain of internal disc disruption. The improvement gained by this treatment method is significantly better than that obtained from conservative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 39 publications
0
37
0
1
Order By: Relevance
“…7,[17][18][19] Regarding the type of complication, for laser, the literature reports spondylodiscitis as the most common, with an occurrence ranging from 0.24% to 1.2%. 15,16,24 In contrast, this series shows radiculitis as the principal complication. This complication is related to the initial stages of the learning curve, incorrect (too deep) anesthesia protocol, and excessive heat from fibers with low irrigation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…7,[17][18][19] Regarding the type of complication, for laser, the literature reports spondylodiscitis as the most common, with an occurrence ranging from 0.24% to 1.2%. 15,16,24 In contrast, this series shows radiculitis as the principal complication. This complication is related to the initial stages of the learning curve, incorrect (too deep) anesthesia protocol, and excessive heat from fibers with low irrigation.…”
Section: Discussionmentioning
confidence: 54%
“…5 The effectiveness of both LS and RF has been reported in several studies, with improvement rates of above 70%. 7,8,11,[13][14][15][16][17][18][19][20][21] Nevertheless, their safety margin and degree of complications continue to create extensive controversies between different surgeons. The purpose of the study was to report and compare the number and grade of major complications present in non-endoscopic thermal discectomy and nucleoplasty, in the treatment of discogenic axial lumbar pain using LS and RF technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Finch et al [32] reported on the use of a flexible radiofrequency electrode (discTRODE; Valleylab, Boulder, CO) in a prospective case-control study to determine the efficacy of radiofrequency heating of painful annular tears. Thirty-one patients underwent the procedure.…”
Section: Percutaneous Intradiscal Radiofrequency Thermocoagulationmentioning
confidence: 98%
“…1 Newer thermal annular procedures include unipolar radiofrequency annuloplasty and bipolar biacuplasty, with only anecdotal studies reported in the literature. [23][24][25] …”
Section: Annular Proceduresmentioning
confidence: 99%